2010
DOI: 10.1186/1471-230x-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2-induced colonic secretion in patients with and without colorectal neoplasia

Abstract: BackgroundThe pathogenesis for colorectal cancer remains unresolved. A growing body of evidence suggests a direct correlation between cyclooxygenase enzyme expression, prostaglandin E2 metabolism and neoplastic development. Thus further understanding of the regulation of epithelial functions by prostaglandin E2 is needed. We hypothesized that patients with colonic neoplasia have altered colonic epithelial ion transport and express functionally different prostanoid receptor levels in this respect.MethodsPatient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
23
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…The method used has previously been described in detail [21, 22]. Correction for media resistance between tips of potential electrodes was carried out just before mounting of biopsies, thus circumventing challenges of edge damage in measuring correct active ion transport.…”
Section: Methodsmentioning
confidence: 99%
“…The method used has previously been described in detail [21, 22]. Correction for media resistance between tips of potential electrodes was carried out just before mounting of biopsies, thus circumventing challenges of edge damage in measuring correct active ion transport.…”
Section: Methodsmentioning
confidence: 99%
“…The function of PGE 2 is highly pleiotropic, as it can regulate the secretion of anions17 and mucus18, GI motility19, and the survival and proliferation of IECs2021. PGE 2 may also contribute to the maintenance of the stem-like properties of IECs through the enhancement of Wnt signalling2223. In addition, PGE 2 is one of the inflammatory mediators upregulated in inflammatory bowel disease (IBD)2425.…”
mentioning
confidence: 99%
“…Lubiprostone does not enhance colonic motor activity, and is unlikely to cause accelerated colonic transit, although may facilitate laxation through its secretory effect [55,57]. A previous study had demonstrated that lubiprostone retarded gastric emptying compared to a placebo, but it accelerated small-bowel and colonic transit time in healthy subjects [29].…”
Section: Pharmacokinetics and Mechanism Of Actionmentioning
confidence: 96%